(untitled) (Journal of Pharmaceutical Negative Results, 2022)
This is a good thing because animals show other organisms how to stay healthy in their environment. Biologists can learn more about a lot ofdifferent biological processes by studying animals that aren’t humans. They can also get new ideas about how other organisms work. A modelorganism called the zebra fish (Danio rerio) has been used to study development and diseases like cancer and cardiovascular disease, as wellas toxicology and drug discovery. Zebra fish have also been used in molecular genetics and genomic research. They are used in toxicologyand biology research because they are a good example of a living thing. Because zebra fish are used to model human diseases, they have a lotmore advantages than other vertebrate models. For example, zebra fish are better than other vertebrate models when it comes to testing largescale genetic mutations and therapeutic chemicals. They are used in toxic genomics and aquaculture as genetic models. They can also be usedto make human illness models based on zebra fish diseases, which can help scientists learn more about how humans get sick. For example,because it’s so easy to keep and breed this little fish, it can be used in a wide range of scientific fields because it has a translucent body.